Незалежні предиктори формування аневризми лівого шлуночка у гострому періоді Q-інфаркта міокарда - Кисельов, Сергій Михайлович (My University, 2015)
З ціллю визначити незалежні предиктори формування гострої аневризми серця обстежено 235 хворих на Q-інфаркт міокарда. Встановлено, що незалежними предикторами формування аневризми лівого шлуночка є тривалість інтервалу QT, індекс сферичності, індекс локальної скорочувальної здатності, час уповільнення потоку раннього діастолічного наповнення лівого шлуночка, рівень матриксної металопротеїнази-9, інтерлейкіну-6 та протеїну С. The problem of prognosis of myocardial infraction (MI) clinical course is one of the most important in modern cardiology. The formation of left ventricle aneurysm is an extremely unfavorable prognostic factor that essentially increases the mortality of patients with myocardial infraction. The aim of research was to define independent predicators of an acute heart aneurysm. Methods. There were examined 235 persons with Q-myocardial infraction. There was assessed prognostic importance of the results of combined daily monitoring of arterial pressure and electrocardiogram, echocardiography, markers of territorial matrix state, system inflammation and hemostasis. Results. Statistically reliable prognostic indices were selected using ROC-analysis. Single- and multi-factor analysis of proportional Cox risks was carried out to define dependent and independent prognostic factors of forming left ventricle aneurysm. Conclusions. In patients with MI in acute period independent pr edicators of forming left ventricle aneurysm are: duration of compensated QT interval, sphericity index, local contractility index, deceleration time of an early diastolic filling flow of the left ventricle, the level of matrix metalloproteinase-9, interleukin-6 and protein C.
Keywords: інфаркт міокарда; аневризма серця; матриксна металопротеїназа-9; інтерлейкін-6; протеїн С; myocardial infraction; heart aneurysm; matrix metalloproteinase-9; interleukin-6; protein C